THE USE OF EXTRACORPOREAL MEMBRANE OXYGENATION IN THE PRACTICE OF CARDIO-PULMONARY RESUSCITATION: OVERVIEW AND PROSPECTS OF THE TECHNOLOGY - O. N. Reznik; A. E. Skvortsov; V. M. Teplov; S. S. Komedev; A. V. Lopota; N. A. Gryaznov; V. V. Kharlamov; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
.